2020
DOI: 10.1371/journal.pone.0228643
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the role of Zn cluster family transcription factor ZcfA in governing development in two Aspergillus species

Abstract: Filamentous fungi reproduce asexually or sexually, and the processes of asexual and sexual development are tightly regulated by a variety of transcription factors. In this study, we characterized a Zn 2 Cys 6 transcription factor in two Aspergillus species, A. nidulans (AN5859) and A. flavus (AFLA_046870). AN5859 encodes a Zn 2 Cys 6 transcription factor, called ZcfA. In A. nidulans, ΔzcfA mutants exhibit decreased fungal growth, a reduction in cleistothecia production, and increased asexual reproduction. Over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…For ST production, fungal strains were incubated in liquid complete medium (CM) at 30 °C for 7 days. To examine the effects of hbxA overexpression, solid MMG (non-inducing), MM with 100 mM threonine (MMT, inducing), or YLC (0.1% yeast extract, 1.5% lactose, 30 mM cyclopentanone) media were used 53 . Escherichia coli DH5α cells were grown in Luria-Bertani medium with ampicillin (100 μg/ml) for plasmid amplification.…”
Section: The Distribution Phylogenetic Analyses and Sequence Logos mentioning
confidence: 99%
“…For ST production, fungal strains were incubated in liquid complete medium (CM) at 30 °C for 7 days. To examine the effects of hbxA overexpression, solid MMG (non-inducing), MM with 100 mM threonine (MMT, inducing), or YLC (0.1% yeast extract, 1.5% lactose, 30 mM cyclopentanone) media were used 53 . Escherichia coli DH5α cells were grown in Luria-Bertani medium with ampicillin (100 μg/ml) for plasmid amplification.…”
Section: The Distribution Phylogenetic Analyses and Sequence Logos mentioning
confidence: 99%
“…In addition, follow-up studies identified the functions of some target genes and these results provide some clues to elaborate on how these TFs can control spore formation and maturation 29 . For example, the VosA-VelB complex controls the expression of fksA , mtfA , sclB , and vadA , thereby fine-tuning β-glucan synthesis, secondary metabolism, oxidative response, and conidial pigmentation 29 , 31 33 , 39 41 . This study further expands the VosA/VelB-mediated regulatory networks involving McrA in A. nidulans .…”
Section: Discussionmentioning
confidence: 99%
“…Discovered and characterized recently in A. flavus and A. nidulans , this Zn2Cys6 TF is essential for the balance between sexual and asexual reproduction. The authors showed that its level of transcripts increased in the Δ vosA mutant of each species [ 75 ].…”
Section: Discussionmentioning
confidence: 99%